PERAN KEPOLISIAN DALAM MELAKSANAKAN ASAS AKUSATOR PADA PROSES PENYIDIKAN (Studi Penelitian Di Kepolisian Resort Langkat) - M. Rinaldo Mahendra; Sumiadi S; Ummi Kalsum (Fakultas Hukum Universitas Malikussaleh, 2022)
The accusator principle is a principle that contains provisions that must be implemented by law enforcement officers in terms of treating suspects in their position as human beings who have dignity. The accusator principle is explicitly regulated in Article 50 paragraph (1) - Article 60 of the Criminal Procedure Code (KUHAP). There are still practices of torture and intimidation against suspects in the investigation process. This study discusses the role of the police in implementing the accusator principle in the investigation process, as well as the obstacles and solutions for investigators in implementing this principle. The research method in this thesis uses an empirical juridical research method with a statutory and case approach. The nature of the research used is descriptive. Sources of data used are primary data and secondary data. The results of the study show that the accusator principle has not been fully implemented because there are still acts of physical and psychological violence against the suspect. The obstacles encountered are investigators who are not professional enough, resulting in actions that are contrary to the accusator principle. In examining a suspect, investigators have difficulty obtaining information from the suspect because the suspect is silent, suddenly gets sick, or is complicated in providing information and is not cooperative. The presence of investigator supervisors is often not in accordance with the objectives because of the assumptions and habits as co-workers, so the supervisory function does not run properly and properly. It is recommended that implementing regulations at each level regulate the plan for a tiered examination in dealing with the criteria for suspects. It is necessary to hold special training for investigators both on a national scale and at the provincial or district/city level so that all investigators can act professionally and truly understand the principle of accusator in their duties.. Keywords : Police, Accusator Principle, Investigation